STUDY THE EFFECT OF SOME INHIBITOR FACTORS ON PRODUCTION OF SOME VIRULENCE FACTORS OF PSEUDOMONAS AERUGINOSA AND THEIR ABILITY FOR ADHESION TO CONTACT LENSES - Flayyih, May; Sweedan, Enass; Mohammed, Luma (Iraqi Journal of Science, 2024)
Two isolates of Pseudomonas aeruginosa were obtained from contact lenses weares with eye infection. P. aeruginosa isolates were able to produce gelatinase, elastase and protease. The P. aeruginosa isolates serotypes were A:p9 and F:P12 . The sensitivity of the isolates to the antibiotics was tested, the results showed that both isolates were resistant of the used antibiotics except Chloramphenicol and Ciprofloxacin. The ability of P. aeruginosa isolates to adhere to soft contact lenses was tested. The effect of the antibiotics )Chloramphenicol and Ciprofloxacin), soft contact lenses care solution, normal saline and sterilization solutions (drops) like Methadin and Nazordin and enzymes (Papain,Neuraminidase) on production of protease and elastase. The results showed that Nazordin and Methadin were reduced the production of protease and elastase (residual activity of protease 47%&42% respectively), and (the residual activity of elastase 42&%49% respectively).The effect of antibiotics (Chloramphenicol,Ciprofloxacin),lens contact care solution , normal salin, Methadin Nazordin and enzymes (papain ,Neuraminidase) on P. aeruginosa adhesion to contact lenses was tested. The results showed that sterilization drop (Nazordin) was more effective ratio on the bacterial adherence, the inhibitory ratio of Nazordin was 90.68%, and the inhibitory ratio of Methadin was 72.06 ℅ of cells from adhesion to contact lenses. While the enzymes (Papain, Neuraminidase ) did not reduce adhesion.